Pengaruh Sumber Daya Alam Terhadap Indikator Sosial Ekonomi - Teuku Muhammad Irfansyah; Uka Wikarya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Natural resource extraction in Kalimantan has long been a cornerstone of both local and national economic development. While such resources can stimulate growth, their impact on socio-economic indicators depends on the intensity of interaction between economic and social dimensions. This study analyzes the effects of coal mining, oil and gas extraction, and oil palm plantations on poverty and open unemployment rates across 55 districts and cities in the five provinces of Kalimantan (West, East, North, South, and Central Kalimantan) over the period 2010 to 2023. Panel data regression is employed, with robustness checks conducted by dividing the analysis into two subperiods: 2010-2016 and 2017-2023. The results show that coal mining has not contributed to reducing either poverty or unemployment. Oil and gas extraction has no significant impact on poverty and has not reduced unemployment during the 2010-2016 period. In contrast, oil palm plantations consistently reduce open unemployment across the entire period and are associated with poverty reduction in the 2017-2023 subperiod. These findings suggest the need for governance reform in the mining sector to improve its contribution to poverty and unemployment reduction, along with stronger policy support for the palm oil sector, which has demonstrated more consistent socio-economic benefits.